Ergebnisse der Albanien-Expedition 1961 des Deutschen Entomologischen Institutes. 43. Beitrag. Hymenoptera: Cleptidae und Chrysididae. - Zimmermann, Stephan (Contributions to Entomology = Beiträge zur Entomologie, 1965)
The present paper deals with the ruby-tailed wasps (Cleptidae and Chrysididae) found in the expedition to Albania by Deutsches Entomologisches Institut. This collection includes 30 specimens of 16 species. One of these species (Cleptes scutellaris Mocsary) is new in the fauna of Albania. Approximately 80 species from Albania are recorded in literature, but in view of our present knowledge of the classification and nomenclature of these families this cannot be accepted without reinvestigating the original findings.